Transduction of the Streptococcus pyogenes bacteriophage Φm46.1, carrying resistance genes mef(A) and tet(O), to other Streptococcus species - Giovanetti, Eleonora; Brenciani, Andrea; Morroni, Gianluca; Tiberi, Erika; Pasquaroli, Sonia; Mingoia, Marina; Varaldo, Pietro E. (Frontiers in Microbiology, 2015)
Фm46.1 — a Streptococcus pyogenes bacteriophage carrying mef(A) and tet(O), respectively encoding resistance to macrolides (M phenotype) and tetracycline — is widespread in S. pyogenes but has not been reported outside this species. Фm46.1 is transferable in vitro among S. pyogenes isolates, but no information is available about its transferability to other Streptococcus species. We thus investigated Фm46.1 for its ability to be transduced in vitro to recipients of different Streptococcus species. Transductants were obtained from recipients of Streptococcus agalactiae, Streptococcus gordonii, and Streptococcus suis. Retransfer was always achieved, and from S. suis to S. pyogenes occurred at a much greater frequency than in the opposite direction. In transductants Фm46.1 retained its functional properties, such as inducibility with mitomycin C, presence both as a prophage and as a free circular form, and transferability. The transductants shared the same Фm46.1 chromosomal integration site as the donor, at the 3’ end of a conserved RNA uracil methyltransferase (rum) gene, which is an integration hotspot for a variety of genetic elements. No transfer occurred to recipients of Streptococcus pneumoniae, Streptococcus oralis, and Streptococcus salivarius, even though rum-like genes were also detected in the sequenced genomes of these species. A largely overlapping 18-bp critical sequence, where the site-specific recombination process presumably takes place, was identified in the rum genes of all recipients, including those of the species yielding no transductants. Growth assays to evaluate the fitness cost of Фm46.1 acquisition disclosed a negligible impact on S. pyogenes, S. agalactiae, and S. gordonii transductants and a noticeable fitness advantage in S. suis. The S. suis transductant also displayed marked overexpression of the autolysin-encoding gene atl.